Correlation of Cultural Activity of River Bank to Tidal River Transportation Function - Boby Rahman (International Conference on Coastal and Delta Areas, 2017)
Mentaya River is a tidal river that is closely related to the coastal and sea. History shows a close relationship between settlements and rivers, in areas of Borneo that have very close relationships between rivers in the formation and development of people and communities. From the development of the people who live on the banks of the river, they can make the river as one of the sources of their life and income sources, both from the aspects of transportation, economic, social and cultural. No one if settlements on the river bank is one characteristic of Sampit City. However, with the progress of the times, there was a decrease in some river culture activities followed by the decline of the Mentaya River function. Based on the settlement condition of Mentaya River, the researcher used the questionnaire sample based on the beginning of the community from 1970-2015 to deeper the knowledge and implementation of the society on river culture and its effect on river transportation function. The research was carried out by Quantitative Rationalistic research method, through correlation analysis technique approach, the result of positive influence and change activity response with different relationship level and influence from some river culture activity to preservation of function of Mentaya Sampit River. Keywords: Tidal River Culture, river bank settlements and River Transportation Function